Fabrication and wear characterization of silicon carbide and copper reinforced aluminium matrix composite. (September 2017) - Vedrtnam, Ajitanshu; Kumar, Anuj
Graphical abstract: Abstract: The present work describes the fabrication of metal matrix composite (MMC) using the stir casting method with Aluminum as a base metal and-, silicon carbide and copper as the reinforcements. The wear behavior of Al-SiC-Cu MMCs for varying reinforcement contents, loads, sliding speeds, and distances were evaluated using a "pin on disk" apparatus, and using a L27 Taguchi orthogonal array. The optimal combination of reinforcement content, load, sliding speed, and distance was obtained using gray relation analysis (GRA) and Taguchi for minimum wear. It was concluded from scanning electron microscopy (SEM) that the nature of wear was mostly abrasive.